Meiofauna as a valuable bioindicator of climate change in the polar regions - Francesca Leasi; Joseph L. Sevigny; Brandon T. Hassett (Ecological Indicators, 2021)
Establishing robust estimates of polar marine biodiversity is important for interpreting future changes in the Arctic; however, despite a recent increase in scientific expeditions, this region remains relatively underexplored. Particularly overlooked in biodiversity assessments are small species, such as protists, fungi, and many small invertebrates that are collectively known as meiofauna. These species contribute to the foundation of food webs and are crucial for the survival of larger species that are economically and socially important. The application of high-throughput sequencing methodologies has proven effective for biomonitoring small metazoan species but has sparingly been applied in the Arctic. We used a metabarcoding approach to assess the diversity of sea ice and sediment-associated metazoans from Utqiaġvik (Barrow), Alaska. Sea ice and sediment samples were collected six times over eight months (January through August) encompassing three seasons (winter, spring, and summer) from polar night to ice-out in August. Biodiversity was assessed as both richness and community composition by incorporating incidence data and phylogenetic distance. Environmental conditions associated with ice, sediment, water, and snow were measured and tested for possible correlations with biodiversity estimates. We found a high number of taxa distributed locally, suggesting that metabarcoding can be effectively applied to Arctic biomonitoring programs. In addition, these results show that season and habitat are significant predictors of meiofaunal biodiversity, supporting hypotheses that meiofauna can be used as a valuable indicator of climate change.